A Short Note on Ancient Heritage Edifices after the 2015 Earthquake - Joshi, Hikmat Raj (Journal of the Institute of Engineering, 2016)
The ancient heritage edifces of Nepal have special characteristics both from technical and architectural point of view. They have gone through several cultural and natural upheavals like tribal invasions and earthquakes. In this paper, the attempts of the people to reinstate them, in the past and how it should be done, in the present context have been presented in a seminal way for further detail development, in the future. Journal of the Institute of Engineering, 2015, 11(1): 189-190